Compact wideband broadside-coupled microstrip-slot bandpass filter for communication applications - Norhudah, Seman; Dyg Norkhairunisa, Abang Zaidel; Zuhaili Amalina, Abd Wahid; Nor Azimah, Mohd Shukor; Tharek, Abd Rahman (Institute of Advanced Engineering and Science, 2017)
This paper proposes a compact size design of wideband bandpass filter (BPF). The broad-side coupling microstrip-slot technique is used to accomplish a good passband response with very low insertion loss across a wideband frequency range. The BPF that is designed using Rogers RO4003C substrate shows a good performance with the respective maximum reflection coefficient and insertion loss of -10 dB and 1.2 dB between 0.92 GHz and 5 GHz. This type of BPF filter is useful in any communication applications.